2015
DOI: 10.1063/1.4936625
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the glass transition of fragile soft colloidal suspensions

Abstract: Microscopic relaxation timescales are estimated from the autocorrelation functions obtained by dynamic light scattering experiments for Laponite suspensions with different concentrations (C L ), added salt concentrations (C S ) and temperatures (T ). It has been shown in an earlier work [Soft Matter 10, 3292 (2014)] that the evolutions of relaxation timescales of colloidal glasses can be compared with molecular glass formers by mapping the waiting time (t w ) of the former with the inverse of thermodynamic t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…These systems do not form  Thomas Palberg palberg@uni-mainz.de crystals. Rather, they assume an amorphous structure in the solid phase through different paths already at low volume fractions [51]. In analogy to the Wigner-crystals formed by spheres through electrostatic repulsion, such states have been termed Wigner-glass by some authors [41].…”
Section: The Topological Approachmentioning
confidence: 99%
“…These systems do not form  Thomas Palberg palberg@uni-mainz.de crystals. Rather, they assume an amorphous structure in the solid phase through different paths already at low volume fractions [51]. In analogy to the Wigner-crystals formed by spheres through electrostatic repulsion, such states have been termed Wigner-glass by some authors [41].…”
Section: The Topological Approachmentioning
confidence: 99%
“…As t w increases, the decay of F s ( q , t ) slows down considerably. Furthermore, the decay of F s ( q , t ) can be described as a two-step process 34 comprising a fast decaying exponential part and a comparatively slower stretched exponential part 31 , 35 , 36 , 44 and can be expressed as Here, τ 1 is the fast or secondary relaxation time (corresponding to the diffusion of a Laponite particle inside the cage formed by the neighbors), τ ww is the structural or primary α -relaxation time (representing its cooperative diffusion to a neighbouring position), β is a stretching exponent, and a is the weight factor for the faster secondary relaxation process 34 . Fits of the experimental data to Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Fragility 4 , 5 of the colloidal glasses is studied by the modified Vogel-Fultcher-Tammann (VFT) equation in which 1/ T is replaced by ϕ (the relevant control parameter for colloidal glasses) 47 . Since Laponite suspensions transform to a non-ergodic state as t w increases, therefore t w has been used as the control parameter to study the Laponite glassy dynamics 31 , 33 36 , 44 , 48 . The fragile behavior of Laponite suspensions is studied by employing the modified VFT equation in which ϕ is replaced with t w 34 , 36 such that the modified VFT equation can be written as follows 33 , 34 , 36 :
Figure 1 ( a ) Self intermediate intensity scattering functions ( F s ( q , t ) decay curves) vs. delay times recorded at various waiting times ( t w ) at θ = 90° ( q = 2.2 × 10 −2 nm −1 ).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, whether the softness does really contribute to the drastic change in the fragility remains controversial. Indeed, in several experiments [36,37,45,46], it was found that the fragility in soft colloids is insensitive to the softness of the interaction potentials. Previous simulations with model soft colloids showed that the drastic variation in m k cannot be reproduced by merely modifying the softness of the potential [37,[47][48][49].…”
Section: Introductionmentioning
confidence: 99%